Singularized educational paths and disability at the National University of Río Cuarto (Praxis Educativa, 2024)
This article arises in the context of the Research Project entitled: Inclusion of students with disabilities at the National University of Río Cuarto. From text to practice (Rector’s Resolution No. 083/2020). The purpose of the writing is to explain theoretically some of the aspects identified in one of the categories of analysis that emerged from the empirical evidence collected. Understanding and explaining the reality in which the group of students with disabilities finds themselves involves delving into the views that the institution has regarding this reality. Therefore, particularly from this situated research and, on this occasion, we will start from understanding how the framework of disability is constituted by focusing the analysis on the concept of singularized educational trajectories reconstructed from the testimonies collected, in the in-depth interviews carried out with different actors who hold management positions in the institution.
Keywords: educational trajectories; university; students; disabilities.